Analisis Manajemen Keselamatan dan Kesehatan Kerja pada Keadaan Darurat Kebakaran di Mass Rapid Transit (MRT) Jakarta - Judea Satrio; Daru Lestantyo; Ida Wahyuni (Jurnal Riset Kesehatan Masyarakat, 2021)
The Jakarta Mass Rapid Transit (MRT) is an urban mass and fast transit transportation system based on electric rail, which is characterized by its ability to carry large volumes of passengers quickly. In its operational service activities, the Jakarta MRT can experience a fire emergency situation. Therefore, a fire emergency response system is needed as an effort of occupational safety and health management in preventing and overcoming fire emergency situations that may occur. This study aims to analyze the fire emergency response system in the Jakarta MRT. This type of research is a descriptive study with a qualitative approach. The data were collected through direct observation and organized online in-depth interviews involving 4 main informants and 2 triangulation informants. The result of this study shows that the Jakarta MRT has a fire emergency response system that includes the fire emergency response policy, fire hazard identification, emergency response team, fire protection systems, life-saving facilities, fire emergency response training, emergency communications, fire safety inspection, fire emergency response procedure, investigation and report, and fire safety audit. However, there are still fire protection systems at the station and in the train that are not available and not in accordance with the applicable standards such as the fire control center, fire elevator, yard hydrant, sprinklers, fire extinguishers, smoke control system, firefighter access, and emergency safety hammer. The researcher suggests the Jakarta MRT provide fire protection systems that are not yet available and adjust the fire protection systems in accordance with applicable standards of laws and regulations.